Hubungan Pengetahuan Ibu dan Dukungan Keluarga dengan Pemberian ASI Eksklusif: The Relationship between Maternal Knowledge and Family Support with Exclusive Breastfeeding - Firyal Faris Naufal; Hafifah Rahmi Indita; Lailatul Muniroh (Amerta Nutrition, 2023)
Background: Various factors have influenced exclusive breastfeeding, but the practice remains low globally. In the Tengger community, several studies have shown that 79% of mothers provide colostrum, but only 60% succeed in practicing exclusive breastfeeding. Another study also showed that the prevalence of exclusive breastfeeding in toddlers was 38%. Objectives: Analyzed the relationship between mothers' knowledge and family support with exclusive breastfeeding for children under two years in Tengger Community. Methods: The study was analytical observational with case-control design. The proposal was outlined in February, and the research was carried out until July 2022. Used the total sampling technique and the sample consisted of 57 infant mothers, 28 mothers in the control group, and 29 mothers in the case group. Conducted in the Tengger community, Pasuruan Regency, East Java. Interview and questionnaire as data collection. Results: Mothers were between 20–34 years old, having good knowledge (67.9%) and good family support (75%). A weak negative correlation existed between maternal knowledge and exclusive breastfeeding (r=-0.05). Very weak positive correlation between family support and exclusive breastfeeding (r=0.139). Among the components of family support, emotional support had a moderately strong positive correlation (r=0.41), the information had a very weak positive correlation (r=0.228), the assessment had a very weak positive correlation (r=0.208), and instrumental had a very weak negative correlation (r=-0.15). These results are from Spearman correlation tests. Conclusion: Higher maternal knowledge has a feeble influence on exclusive breastfeeding, but more excellent family support has a more substantial influence. Maternal knowledge and family support play vital roles in promoting exclusive breastfeeding.